Correlat ion and Path Co-eff icient Analysis for Yield and it’s At tribut ing Traits in Diverse Genotypes of Cowpea (Vigna unguiculata L.) - Khandait, Ramnarayan; Jain, P. K.; Prajapati, Sunil; Singh Dangi, Avtar (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted at Vegetable Research Farm, Collage of Agriculture, JNKVV, Jabalpur (Madhya Pradesh), during kharif season of 2014-15. The experimental material consisting of 15 genotypes of cowpea laid out in Randomized Complete Block Design with three replications. The present study resulted that, significant positive phenotypic correlation of pod yield plant-1 was observed with pods plant-1 (0.589), days to first flowering (0.415), seeds pod-1 (0.395), number of flower cluster plant-1 (0.372) and pod length (0.304). Seed yield plant-1 was resulted significant and positive correlation with pod yield plant-1 (0.395) indicating that these characters are the primary yield determinant in cowpea. Path coefficient analysis of different characters contributing towards pod yield plant-1 resulted that number of pods plant-1 (2.108) had highest positive direct effect followed by pod weight (2.054), number of flower cluster-1 (0.347), pod width (0.298), number of branches at 90 DAS (0.256), number of flower cluster plant-1 (0.154), days to first picking (0.128), plant height at 90 DAS (0.081) and pod length (0.033). Whereas, days to first flowering (-0.061) had the maximum negative direct effect on pod yield plant-1 followed by days to 50% flowering (-0.121), number of seeds pod-1 (-0.563) and pods cluster-1 (-0.712). Hence, simultaneous selection for these characters can be made for the improvement of cowpea yield.